Literature Review: Teachers’ and Students’ Language Attitude Towards the Use of Indonesian Language in the Japanese-Speaking Classroom - Setiyani Wardhaningtyas; Aceng Rahmat; Liliana Muliastuti (Universitas Negeri Semarang, 2023)
This study aims to discover the variety and research trends for L1 language use in the L2 classroom. This study used library research or literature review to collect and process the data. The data originated from national and international articles, journals, and documents. Many sources have shown the result of the study stating that using a first language in learning a foreign language, especially in the speaking classroom, has made teachers and students get several positive attitudes. According to some research, the three characteristics of positive attitudes toward using the Indonesian language in the speaking classroom-language involve loyalty, language pride, and language awareness of norms that both teachers and students highlight. The two methodologies most commonly used in linguistic attitude studies are direct and indirect measures. The results of a survey of linguistic attitudes indicate whether or not students are effective at learning a language. Attitude is known, not innate. Students can improve their favourable language attitudes toward other languages through specific educational activities Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education JournalJapanese Speaking ClassroomJapanese Literature ReviewJapanese Studies